The Effect of Two Foot Forwads, in Out and Two Foot Sideways Training on Access and Speed of Students of MTS Badrussalam Surabaya - Teguh Sholikin; Oce Wiriawan; Sapto Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Many students at MTs Badrussalam who take extracurricular activities lack agility and speed. Agility and speed serve to support students during extracurricular activities, students who do exercises programmatically and regularly can improve agility and speed. Ladder drill is one of the exercises to improve agility and speed. In this study, the aim was to find out that agility ladder training increased agility and speed. The results of this study are expected to be used by practitioners as evaluation material for the development of knowledge in the field of science that has been carried out with programmatic training in order to increase agility and speed. The research method uses quantitative research with quasi-experimental methods. This research design uses a randomized control group pretest-posttest design. In this design, thirty samples were divided into three groups which were given different treatments. The analysis used is the average (mean), standard deviation, normality test and ANOVA (Analysis of variance). The results of this study after being tested with ANOVA is that there is a significant effect on agility ladder two foot forwards, agility ladder in and out and agility ladder two foot sideways exercises on agility with sig (0.048), (p <0.05) then also there is a significant effect on speed with sig (0.041) (p<0.05). Based on the LSD test, the most influential of ladder drill exercises on agility is 1). Ladder drill two foot side ways. 2). Ladder drill in and out, 3). The two foot forwards ladder drill exercise and the speed that affects the ladder drill exercise are 1). Ladder drill two foot forwards exercise, 2). Ladder drill in and out, 3). Ladder drill two foot side ways.